Numerical Analysis of Solar Hybrid Photovoltaic Thermal Air Collector Simulation by ANSYS - Abdullah, Amira Lateef; Misha, Suhaimi; Tamaldin, Noreffendy; Mohd Rosli, Mohd Afzanizam; Abdulameer Sachit, Fadhil (CFD Letters, 2021)
Solar energy is one of the renewable energy sources which have potential for future energy applications. The current technology converts solar energy into electricity and heat respectively. The aim from the paper to increases the PV efficiency by using duct of air under the PV panels to help reduce the temperature of the PV cells, an effort was made to simulate and evaluate the overall performance of a hybrid photovoltaic thermal (PVT) air collector using computational fluid dynamics (CFD) software. The numerical analysis of the flow and heat transfer in hybrid PVT systems is computationally complicated. Based on numerical analysis, the performance of a solar hybrid PVT air collector was studied. The numerical simulation was performed using a commercial software ANSYS FLUENT 19.1. The electrical energy conversion from the solar cells was calculated with a user defined function. The numerical results were validated with the experimental results from the literature. The results showed a good agreement between the experimental and simulated results for outlet air temperature and PV cell temperature. Using a validated model, the effects of mass flow rate and duct depth on the performance of solar hybrid PVT collector were studied and optimum values were identified. The results indicated that the reduction in the depth of air channel increases the thermal efficiency, but it has no considerable effect on the electrical efficiency. The increase of the mass flow rate of air increases the thermal efficiency, but a slight enhancement is required for the generation of electrical power by PVT.